ANALYSIS OF RAINWATER INFILTRATION IN VARIOUS SOIL EMBANKMENTS IN LABORATORY TESTING - Putra, Aldio Fikhri Maulida; Andayono, Totoh (Teknik Sipil Universitas Negeri Padang, 2023)
This research is motivated by the frequent occurrence of continuous puddles in a particular area, resulting in the loss of property, livestock, crops, and even human lives. One of the causes of this inundation is continuous rainfall in a specific location. Therefore, efforts must be made to address waterlogging. The purpose of this research is to assess the water infiltration capacity into the soil using an artificial infiltration tool. There are various methods used to facilitate water infiltration into the soil, one of which is the absorption well. This study is an experimental method that tests the performance of the rate of water infiltration using an artificial infiltration tool in laboratory testing at the Department of Civil Engineering's Building Materials and Soil Mechanics Laboratory, Faculty of Engineering, Universitas Negeri Padang. The results of this test provide the rate of rainwater infiltration and rainwater infiltration capacity values from several soil embankments. The selected embankment soils were from the Lubuk Alung, Sungai Sariak, Duku Teluk Kabung quarries, and the Gunung Sarik quarry. Based on the conducted analysis, the highest rainwater infiltration capacity value was obtained from the embankment soil from the Sungai Sarik quarry, amounting to 0.8 mm/hour during the first rainfall and 1.3 mm/hour during post-rainfall, with a water infiltration volume of 150,000 m3/hour/km2.